The Uphill Battle for Iranian Women in the Labour Market - Taheri, Elham (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
Economic sanctions are one of the political tools that one country or group of countries, applies in other countries for putting them under pressure because of a variety of political and social issues. Most of the studies tried to measure the impact of sanctions on different economic sectors or on the wellbeing of the society (e.g. Neuenkirch and Fneumeier, 2014; Peksen, 2011). There are very few of them investigating the gender impact of the sanctions (e.g. Drury and Peksen, 2012). Previous studies on the impact of economic sanctions show that the overall impacts of economic sanctions are negative. The aim of this paper is to investigate the effect of economic sanctions on women’s economic rights in Iran. The study will cover the years from 1990 to 2013. To investigate the effect of economic sanctions on women’s economic rights; female labor participation rate; as an index measurement of women’s economic rights, regressed on economic sanctions (size), GDP per capita, and economic cost of sanctions. Results indicate that economic sanction has negative impact on women’s economic rights.

ÖZ: Ekonomik yaptırımlar, belli ya da bir grup ülkeler tarafından başka ülkelere uygulanan çeşitli politik ya da sosyal nedenli ambargolardır. Literatürdeki çeşitli çalışmalar yaptırımların farklı ekonomik sektörler ya da toplumun genel refahı üzerindeki etkisini ölçmektedir (ör. Neuenkirch ve Fneumeier, 2014; Peksen, 2011). Aralarından sadece küçük bir kısmı yaptırımların toplumsal cinsiyet etkisini ölçmektedir (ör. Drury ve Peksen, 2012). Ekonomik yaptırımların etkileriyle ilgili önceki çalışmalar söz konusu etkinin negatif oldugunu göstermektedir. Bu çalışmanın amacı ekonomik yaptırımların İranlı kadınların ekonomik hakları üzerindeki etkisini ölçmektir. Çalışma 1990’dan 2013’e kadar olan zaman aralığını içermektedir. Ekonomik yaptırımların kadınların ekonomik hakları üzerindeki etkilerini ölçmek için, kadınların iş gücüne katılım oranı bir endeks ölçüm aracı olarak ekonomik yaptırımların boyutu, fert başına GSYİH ve ekonomik yaptırımların maliyeti üzerine regresyon edilmiştir. Ampirik veriler ekonomik yaptırımların Iranlı kadınların ekonomik hakları üzerinde de çeşitli negatif etkiler yarattığını doğrulamıştır.
Doctor of Philosophy in Economics. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2022. Co-Supervisor: Prof. Dr. Cem Esref Payaslıoğlu and Supervisor: Prof. Dr. Fatma Güven Lisanile
Keywords: Thesis Tez; Economics Department; Women in economic development--Women Empowerment--Iran; Women in economics; Businesswomen--Women Entrepreneurship--Iran; Female labour force participation; Iran; gender norms; gender wage gap; glass ceiling effect; care work; occupational gender segregation